1998
DOI: 10.1128/aac.42.7.1702
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA Mutation Associated with Tetracycline Resistance in a Gram-Positive Bacterium

Abstract: A genetic basis for tetracycline resistance in cutaneous propionibacteria was suggested by comparing the nucleotide sequences of the 16S rRNA genes from 16 susceptible and 21 resistant clinical isolates and 6 laboratory-selected tetracycline-resistant mutants of a susceptible strain. Fifteen clinical isolates resistant to tetracycline were found to have cytosine instead of guanine at a position cognate with Escherichia coli 16S rRNA base 1058 in a region important for peptide chain termination and translationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(94 citation statements)
references
References 27 publications
3
86
1
2
Order By: Relevance
“…The gene tet(U) is responsible for low-level tetracycline resistance by unknown means (Ridenhour et al, 1996). Point mutations within the 16S rRNA (Ross et al, 1998) and mutations that alter the permeability of the porin channels (Bolhuis et al, 1997) also increase tetracycline resistance.…”
Section: How Bacteria Exhibit Resistancementioning
confidence: 99%
“…The gene tet(U) is responsible for low-level tetracycline resistance by unknown means (Ridenhour et al, 1996). Point mutations within the 16S rRNA (Ross et al, 1998) and mutations that alter the permeability of the porin channels (Bolhuis et al, 1997) also increase tetracycline resistance.…”
Section: How Bacteria Exhibit Resistancementioning
confidence: 99%
“…This decline was due to the emergence of resistant strains of bacteria. A number of mechanisms have been suggested including; reduction of the intracellular concentration of the compound through active efflux [22], disruption of the tetracycline-ribosomal interaction by ribosomal protection proteins (RPPs) [23], enzymatic inactivation of the drug through mono-hydroxylation [24] and alteration of the target site through 16S RNA mutation [25].…”
Section: Resistancementioning
confidence: 99%
“…Though tetracycline resistance in isolates of Propionibacterium acnes has been reported since the 1980s from various parts of the world [56][57][58], no systematic study to characterize the mechanism was conducted until 1998, when Ross et al [59] showed a point mutation (G ? C) at position 1,058 in 16S-rRNA to be responsible for the resistant phenotype.…”
Section: Target Modificationmentioning
confidence: 99%